Accelerators in Silicon Valley Building Successful Startups - Ester, Peter (Amsterdam University Press, 2017)
In this book Silicon Valley expert Peter Ester describes how these 'schools of startup entrepreneurship' operate and how they empower startups. He interviewed over twenty Silicon Valley accelerators. They are analyzed in terms of mission, selection policy, technology focus, target groups, program features, funding, mentoring and training, and startup showcases. What can Europe and other regions and countries learn from how Silicon Valley accelerators help startups to become successful companies? This book gives the answer. Accelerators in Silicon Valley is a book for entrepreneurs, startup founders, policymakers, practitioners, scholars, and students who share a fascination for building the new startup economy.